1982
DOI: 10.1152/jappl.1982.53.6.1576
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response effects of atropine on thermal stimulus-response relationships in asthma

Abstract: To determine how cholinergic blockade modifies the stimulus-response relationships to thermal provocations, we had seven asthmatics perform increasing levels of eucapnic hyperventilation of subfreezing air (-10.6 +/- 1.9 degrees C) after pretreatment with aerosols of saline and atropine in doses of 0.25, 0.5, 1.0, 3.0, and 6.0 mg. Testing was performed on 5 separate days with both placebo and a single dose of drug. In control experiments, increasing ventilation produced a progressive decrease in the 1-s forced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Indeed, in comparison to salbutamol, i. v. atropine (9] provides relatively little protection against AIB. These results are consistent with human studies that have demonstrated a relatively minor role for muscarinic mediated pathways in EIA [17][18][19].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, in comparison to salbutamol, i. v. atropine (9] provides relatively little protection against AIB. These results are consistent with human studies that have demonstrated a relatively minor role for muscarinic mediated pathways in EIA [17][18][19].…”
Section: Discussionsupporting
confidence: 91%